تجارتی معاملات میں ترغیبات ومراعات کی انواع و اقسام ،شریعت کی روشنی میں تحقیقی مطالعہ - Hafiza Humaria kouser (ایقان, 2018)
Wherever person goes, he finds unless it finds advertisement tools in various shapes and sizes. These ads, which have become an important pattern in the life of traders are indispensable for them than in contemporary reality. But now companies are specializing in the production of these ads and incentives, taking advantage of all the modern means of magazines and broadcasting video and audio formats and even mobile internet services.  Each of these companies have their own philosophy of it, some of which consider the legitimate controls in advertisements but other are to make money regardless of the appropriateness of these ads or following the controls of legitimacy and this research aims at highlighting the most important of these Islamic perspective controls which must be adhered when designing these commercials ads.  Islam regulates the trade system and provides a sound guideline to its followers. It has forbidden all the malpractices being exercised in business and its advertisement. The research talks about the commercial advertisements, their types, aims and the opinions of Islamic experts about them. Besides, the research proves that advertisement is permissible according to shariah.